2019
DOI: 10.1016/j.antiviral.2019.02.006
|View full text |Cite
|
Sign up to set email alerts
|

The isoquinoline alkaloid berberine inhibits human cytomegalovirus replication by interfering with the viral Immediate Early-2 (IE2) protein transactivating activity.

Abstract: The identification and validation of new small molecules able to inhibit the replication of human cytomegalovirus (HCMV) remains a priority to develop alternatives to the currently used DNA polymerase inhibitors, which are often burdened by long-term toxicity and emergence of cross-resistance. To contribute to this advancement, here we report on the characterization of the mechanism of action of a bioactive plant-derived alkaloid, berberine (BBR), selected in a previous drug repurposing screen expressly devise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…Lunganini et al showed that BBR interferes with the transactivating function of the HCMV IE2 protein. IE2 plays a critical role in the progression of HCMV replication and in viral pathogenesis and reactivation from latency [74]. It is the most important HCMV regulatory protein and a strong transcriptional activator of viral and cellular gene expression.…”
Section: Activity Of Bbr Against Members Of the Families Herpesviridamentioning
confidence: 99%
“…Lunganini et al showed that BBR interferes with the transactivating function of the HCMV IE2 protein. IE2 plays a critical role in the progression of HCMV replication and in viral pathogenesis and reactivation from latency [74]. It is the most important HCMV regulatory protein and a strong transcriptional activator of viral and cellular gene expression.…”
Section: Activity Of Bbr Against Members Of the Families Herpesviridamentioning
confidence: 99%
“…Assay optimization identified conditions using the stable cell-line that expresses EGFP under the control of the IE2-dependent UL54 early promoter as suitable for screening purposes [364]. A 2320 bioactive compound library including all FDA-approved drugs was screened and six hit compounds have so far been selected for further study [364,381,382]. These hit compounds are deguelin (DGN), nitazoxanide (NTZ), thioguanosine (TGN), alexidine dihydrochloride (AXN), manidipine dihydrochloride (MND) and berberine (BBR).…”
Section: Ie2 Inhibitorsmentioning
confidence: 99%
“…Identified inhibitors of IE2-dependent transactivation do not inhibit IE1-dependent transactivation and are thus specific to IE2 not IE1 function [364,382,383]. IE1 s function as an IFN antagonist has been targeted for drug discovery via a modular cell-based screening platform designed to identify compounds that inhibit a viral IFN antagonist choice [373].…”
Section: Ie1 Inhibitorsmentioning
confidence: 99%
“…Throughout the years, distinctive techniques have been accounted for the development of the tetrahydroisoquinoline unit [91]. The isoquinoline alkaloid berberine represses human cytomegalovirus replication by meddling with the viral Immediate Early-2 (IE2) protein transactivating action [92]. Isoquinoline alkaloids and indole alkaloids seem to have an immediate enemy of atherosclerotic impact in ApoE−/− mice [93].…”
Section: Pyrrole: Stachydrinementioning
confidence: 99%